Analysis of whole genome sequence of strain "0" of avian infectious laryngotracheitis virus - A. A. Kozlov; N. G. Zinyakov; S. N. Kolosov; N. S. Mudrak; I. A. Chvala (Ветеринария сегодня)
Data on identification and analysis of whole genome nucleotide sequence of strain «O» of avian infectious laryngotracheitis virus are demonstrated. In the process of the whole genome sequence mapping a number of unique and significant nucleotide properties has been identified in genes that code surface proteins responsible for interacting with cell receptors. Strain «O» has been demonstrated to belong to phylogenetic group 1 subgroup 1 (1.1). Genetic relatedness of domestic strain «0» to other vaccine strains widely used in global poultry industry such as Serva, Cover, Hudson and Fowl laryngo has been determined. The mapped nucleotide sequence has been deposited in the international GenBank database under the accession number KU128407. It is the first complete genetic characterization of the domestic vaccine strain.